Fatigue and Its Relationship with Age: A Study of Indonesian Computer-Using Employees in Higher Institution - Syamsul Gultom; Endriani, Dewi; Harahap, Agustin Sastrawan (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, more and more people are using computers for work, particularly among office workers. There is a high risk of fatigue during working time or after that. This fatigue condition might be experienced physically and mentally by the workers. Numerous studies have examined fatigue in employees working physically, but the purpose of this research is to recognize mental and physical fatigue for employees working with age-related computers. This study is a quantitative study with forty-one employees as the participants. The study took place in one of the government universities in Indonesia. Physical fatigue was assessed using the Whole Body Reaction Tester (WBRT) and emotional fatigue (EF) was assessed using the Bourdon Wiersman Test. The data were tested by normality, homogeneity, and T-tests. The results showed that the elderly group experienced visual physical fatigue while the younger group experienced audio physical fatigue. Some of the participants felt secure with mental fatigue at work speed and had issues with mental fatigue at work accuracy and consistency. Further research needs to be carried out in order to determine the causes of these problems.